A preliminary response from the Faculty of Psychology students of the University of Cuenca to the modified EFL teaching approach - Bernal A., Marcelo; Feyen, Jan (Maskana, 2017)
English teachers in Ecuadorian universities, like teachers in many non-native English-speaking countries, face the challenge of dealing with uninterested, unmotivated students, even when intermediate proficiency of English is a basic requirement for graduation. As from the end of 2014, the Faculty of Psychology of the University of Cuenca modified the English as a Foreign Language (EFL) instruction at the three proficiency levels of English learning, by linking the training in reading to the reading of major related material and stimulating the students to practice actively the four English language skills outside the classroom using website and video hosting sites. At the end of 2016, the students’ impressions of being exposed to the modified way of student-centered instruction were assessed using a questionnaire. A total of 106 students completed online the 10-question survey. Results showed the enthusiasm of the students towards the modified more dynamic and interactive mode of EFL instruction; appreciated that more autonomy and responsibility were given to the students, and suggested that focus on grammar should not be neglected. An important side effect of the approach was the indirect harnessing of listening, writing, reading and speaking skills as well as skills in the reading and analysis of thematic research papers; considered an important benefit for the thesis project.